2015
DOI: 10.3389/fimmu.2015.00108
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Treatment Decreases the Number of CD14-Expressing Cells in Porcine Milk Which Correlates with Several Intestinal Immune Parameters in the Piglets

Abstract: Modulating the mucosal immune system of neonates by probiotic treatment of their mothers is a promising approach which can only be investigated through the use of animal models. Here, we used sows and their piglets to investigate the impact of a bacterial treatment on the sow’s milk and on the neonate piglet intestinal immune system. In previous experiments, feed supplementation of sows with the probiotic Enterococcus faecium NCIMB 10415 during pregnancy and lactation had been shown to affect intestinal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Hence, providing probiotics at this point could potentially permit the establishment of early and life-long health benefits (Kenny et al, 2011). Sows should be given more importance here, as many studies have shown how introducing probiotics in the sow diet is an effective way to modify the gut ecosystem and the health of piglets (Alexopoulos et al, 2004;Bohmer et al, 2006;Apic et al, 2014;Siepert et al, 2014;Kritas et al, 2015;Scharek-Tedin et al, 2015). Alternatively, the introduction of probiotic strategies via 'creep feed' is increasingly being studied (Alexopoulos et al, 2004;Shim et al, 2005;Giang et al, 2010).…”
Section: How To Improve the Use Of Probiotics In Early Life Stagesmentioning
confidence: 99%
“…Hence, providing probiotics at this point could potentially permit the establishment of early and life-long health benefits (Kenny et al, 2011). Sows should be given more importance here, as many studies have shown how introducing probiotics in the sow diet is an effective way to modify the gut ecosystem and the health of piglets (Alexopoulos et al, 2004;Bohmer et al, 2006;Apic et al, 2014;Siepert et al, 2014;Kritas et al, 2015;Scharek-Tedin et al, 2015). Alternatively, the introduction of probiotic strategies via 'creep feed' is increasingly being studied (Alexopoulos et al, 2004;Shim et al, 2005;Giang et al, 2010).…”
Section: How To Improve the Use Of Probiotics In Early Life Stagesmentioning
confidence: 99%
“…Few studies suggest a positive impact of sow milk on the intestinal microbiota and immune system of the piglets 39,40 and that certain probiotics given to sows may alter the microbiota composition and immune status of their offspring. 41,42 The only source of nutrients for the new-born piglet is milk, which contains numerous growth factors, microbial antigens and host antibodies e.g., directed against certain pathogens and contributing to passive immunisation in the offspring. 43,44 Interestingly, antibodies against TcdA have been identified in human blood serum 45 which may protect against CDI.…”
Section: Neonatal Microbial Programming Through Mother-offspring Assomentioning
confidence: 99%
“…A recent study further suggests that this early-life effect on the immune response may be promoted not only through the transfer of the probiotic itself but also through immunoactive compounds (i.e. CD14 expressing epithelial cells) from the probiotic-fed mother via the milk (Scharek-Tedin et al 2015). Table 4).…”
Section: Prevention Of Diarrheamentioning
confidence: 99%